2012
DOI: 10.1016/j.juro.2012.07.036
|View full text |Cite
|
Sign up to set email alerts
|

Clustering of UPOINT Domains and Subdomains in Men with Chronic Prostatitis/Chronic Pelvic Pain Syndrome and Contribution to Symptom Severity

Abstract: UPOINT domain criteria capture a homogeneous group for each domain except organ specific, in which bladder and prostate diverge. Clustering of domains specific to the pelvis (urinary, organ specific and tenderness) vs systemic domains (neurologic, infection and psychosocial) implies 2 patient populations that may differ in pathophysiology and treatment response. The primary drivers of pain in patients with chronic pelvic pain syndrome are pelvic floor tenderness, depression and catastrophizing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 21 publications
1
23
0
2
Order By: Relevance
“…Using the UPOINT classification system, 25% of patients felt helpless or hopeless [22]. In contrast to this study, the following studies used the standardized Pain Catastrophizing Scale [23] to measure patients' cognitive style.…”
Section: (1) Pain Catastrophizing Cognitionsmentioning
confidence: 95%
See 1 more Smart Citation
“…Using the UPOINT classification system, 25% of patients felt helpless or hopeless [22]. In contrast to this study, the following studies used the standardized Pain Catastrophizing Scale [23] to measure patients' cognitive style.…”
Section: (1) Pain Catastrophizing Cognitionsmentioning
confidence: 95%
“…In fact, a recent analysis found that 24% of patients had clinically relevant depression [22]. Furthermore, the degree of depression significantly predicted CP/CPPS symptom severity [43,50] and patients' QoL [50].…”
Section: (I) Depressionmentioning
confidence: 99%
“…Painful filling is described as pain that worsens with the degree of bladder filling. The pain may be relieved at least partially by urination [26][27][28]. Painful urgency is described as the urge to urinate due mainly to pain, pressure, or discomfort, but not to fear of incontinence [26].…”
Section: Bladder-specific Features and Diagnosis Of Bps/icmentioning
confidence: 99%
“…Therefore, it would be more prudent to include bladder-specific features in addition to prostate-specific findings in the criteria for organ-specific domain when performing UPOINT-based evaluations in men suspected of having chronic pelvic pain. Samplaski et al [27] characterized patients diagnosed with CP/CPPS using UPOINT domains and subdomains, and the organ-specific domain was subdivided into bladder (organ specific-bladder) and prostate (organ specific-prostate). The organ specific-bladder domain was positive in 33% of their patients.…”
Section: Prudent Approach To Chronic Pelvic Pain In Malesmentioning
confidence: 99%
“…Lately, the UPOINT system has been used to look at gathering of symptoms, to try to distinguish a common cause for some groups of patients. Two clusters have demonstrated the analysis of men with CP/CPPS using the UPOINT system, a 'systemic group' of infection, neurologic, and psychosocial and a 'pelvic' group with the domains of organ specific, urinary, and tenderness [8].…”
Section: Introductionmentioning
confidence: 99%